2007
DOI: 10.1038/nm1626
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CD36 links hyperlipidemia, oxidant stress and a prothrombotic phenotype

Abstract: Dyslipidemia is associated with a prothrombotic phenotype; however, the mechanisms responsible for enhanced platelet reactivity remain unclear. Proatherosclerotic lipid abnormalities are associated with both enhanced oxidant stress and the generation of biologically active oxidized lipids, including potential ligands for the scavenger receptor CD36, a major platelet glycoprotein. Using multiple mouse in vivo thrombosis models, we now demonstrate that genetic deletion of Cd36 protects mice from hyperlipidemia-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
493
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(520 citation statements)
references
References 46 publications
24
493
1
2
Order By: Relevance
“…Thus, PMVs may be important sources of platelet activation by oxidative stress, which initiates the coagulation process in atherothrombosis. CD36, a class B scavenger receptor, promotes platelet activation (10,11). It is expressed in platelets, monocytes and several other cells and mediates many pathophysiological processes by binding with various oxidized phospholipids, apoptotic cells and certain pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PMVs may be important sources of platelet activation by oxidative stress, which initiates the coagulation process in atherothrombosis. CD36, a class B scavenger receptor, promotes platelet activation (10,11). It is expressed in platelets, monocytes and several other cells and mediates many pathophysiological processes by binding with various oxidized phospholipids, apoptotic cells and certain pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of P-selectin protein and P-selectin-dependent adhesion of leukocytes are also reported in ApoE -/-mouse aortic segments [177]. Moreover, it has been suggested that oxPLs could stimulate formation of platelet-monocyte aggregates, an event that may play a role in the pathogenesis of vascular diseases, by enhancing P-selectin expression [178].…”
Section: Primary Role In Stimulating Adhesion Of Monocytes To the Endmentioning
confidence: 91%
“…Recognition of oxidatively modified lipids on the surface of cell membranes and lipoprotein particles plays an important role in numerous innate immune functions and can trigger diverse cellular processes (25)(26)(27)(28)(29)(30)(31)(32). Over the past several years, much effort has focused on our understanding of the chemical and structural nature of oxPL ligands recognized by macrophage pattern recognition receptors.…”
Section: Oxpc Within the Lipid Component Of Oxldl And Oxidized Membramentioning
confidence: 99%
“…Most important is likely the rendering of structurally specific and important functional groups of biological signaling molecules into an anatomic location on the cell surface where receptor engagement and subsequent signaling may occur. For example, CD36 recognition of specific oxPL may not only trigger macrophage phagocytosis (13,14,41), foam cell formation, or other intracellular signaling cascades within macrophages (21,33), but also has been linked to alteration in platelet reactivity and in vivo rates of thrombosis (29). The platelet-activating factor receptor similarly recognizes numerous oxPC species with truncated oxidized fatty acid groups at the sn-2 position (48,49), species that will possess oxidatively truncated fatty acyl groups protruding into the aqueous compartment (22).…”
Section: The Lipid Whisker Modelmentioning
confidence: 99%